A Critical Discourse Analysis of Trump’s Speech on Voter Fraud Claims - Faza Hannan Purinanda; Anggi Rizky Firdhani; Khoirun Nisaa' Arnoi; Mentari Antika Putri (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2025)
Claiming that “this may be the most important speech I’ve ever made,” this speech was one of the most noteworthy turning points of the 2020 United States presidential election. This paper aims at analyzing Trump’s speech on voter fraud claims that was released on December 2, 2020 from a critical discourse perspective. This descriptive qualitative research describes and investigates the main features, the main points of concern, and the objectives tried to achieve by delivering the speech. The result of the study shows that the main features of Trump’s political discourse include simplicity, repetition, parataxis, frames, deictics, hyperboles, inarticulation, and hearsay evidence. These features reflect Trump’s personality as well as his supporters’ characteristics. Regarding the main points of the discourse, there are several issues, including pandemic, swing states, mail-in ballots, and rigged system, that Trump tries to convey. There are also further implications or objectives that Trump tries to achieve by releasing the speech: keeping loyal supporters and avoiding prosecution.